The Effect of Servant Leadership and Organizational Culture on Employee Performance PT United Tractors - Minggus Pradito, Ayi Ahadiat, Habibullah Jimad (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This study aims to determine the effect servant leadershipand organizational culture towards employees of PT United Tractors. This study resulted in a significant effect of servant leadership and organizational culture on the employees of PT United Tractors. The effect of servant leadership is greater than organizational culture on performance. Purpose To know the influence of influence servant leadership and organizational culture towards employees of PT United Tractors. Method The research sample amounted to 340 and the survey was conducted online and Research processed using multiple linear regression. Result This study produces a significant effect of servant leadership and organizational culture towards employees of PT United Tractors. The effect of servant leadership is greater than organizational culture on performance. Limitation The research sample is limited and the object of research is only one company so that it cannot be generalized to other groups of companies. In addition, the use of multiple linear regression only produces a direct effect on the independent variable with the dependent variable so that the interaction between variables cannot be known. Contribution This research is expected to provide additional references for research with the topic servant leadership and organizational culture on performance.